Capsular antibodies induce type-specific phagocytosis of capsulated Staphylococcus aureus by human polymorphonuclear leukocytes. - Karakawa, W W (1988)
Capsular types 5 and 8, which account for about 70% of Staphylococcus aureus strains isolated from the blood of patients, resisted in vitro phagocytosis by human polymorphonuclear leukocytes (PMN). Antisera and monoclonal antibody to type 5 and 8 capsular polysaccharides (CPS) induced type-specific in vitro phagocytosis of capsulated organisms by PMN. Antibodies directed against the O-acetyl moiety of the type 8 CPS were more effective in inducing phagocytosis of type 8 organisms by PMN. Either type-specific antiserum or monoclonal antibody reactive with the native O-acetylated type 8 CPS was most effective in inducing in vitro phagocytosis of type 8 organisms by PMN. These results provide further evidence that CPS of S. aureus are associated with host immunity to this organism.